2006
DOI: 10.1152/ajpregu.00295.2005
|View full text |Cite
|
Sign up to set email alerts
|

Altered arachidonic acid metabolism impairs functional vasodilation in metabolic syndrome

Abstract: Xiang, Lusha, Jay S. Naik, Benjamin L. Hodnett, and Robert L. Hester. Altered arachidonic acid metabolism impairs functional vasodilation in metabolic syndrome. Am J Physiol Regul Integr Comp Physiol 290: R134 -R138, 2006. First published September 15, 2005 doi:10.1152/ajpregu.00295.2005.-These studies tested the hypothesis that in obese Zucker rats (OZRs), a model of metabolic syndrome, the impaired functional vasodilation is due to increased thromboxane receptor (TP)-mediated vasoconstriction and/or decrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
71
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(78 citation statements)
references
References 32 publications
7
71
0
Order By: Relevance
“…Thus the decreased levels of NO noted in obesity may primarily reflect an increased scavenging via reactive oxygen species, resulting in the production of substances such as peroxynitrite [71,74]. When arachidonic acid is introduced to the system, vasodilatory responses are attenuated in both gracilis and spinotrapezious arterioles of the OZR in comparison to the LZR [73,75]. The impaired responses appear to operate partially via an elevation in oxidant stress, but additional signaling pathways independent of acute alterations in oxidant tone appear to also be involved.…”
Section: Vasodilationmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus the decreased levels of NO noted in obesity may primarily reflect an increased scavenging via reactive oxygen species, resulting in the production of substances such as peroxynitrite [71,74]. When arachidonic acid is introduced to the system, vasodilatory responses are attenuated in both gracilis and spinotrapezious arterioles of the OZR in comparison to the LZR [73,75]. The impaired responses appear to operate partially via an elevation in oxidant stress, but additional signaling pathways independent of acute alterations in oxidant tone appear to also be involved.…”
Section: Vasodilationmentioning
confidence: 99%
“…More recently, increased levels of vasoconstrictor prostanoids have also been suggested as a possible mechanism for the decreased vascular perfusion and dilator reactivity within obesity and the metabolic syndrome [88]. In the OZR, an increase in vasodilation was noted when the prostaglandin H2/thromboxane A2 receptor antagonist SQ-29548 was administered, suggesting that a chronic basal vasoconstrictor influence, mediated via the PGH2/TxA2 receptor may contribute to impairments in organ perfusion and dilator reactivity [75]. These changes to endothelial vasoconstrictor response with obesity may show an initial effect, while neurological mechanisms may show a longer lasting systemic role [89].…”
Section: Vasoconstrictionmentioning
confidence: 99%
“…Additionally, the cremaster muscle was stimulated to contract for 3 min at both 1-and 3-Hz contractions by using electrodes placed on opposite sides of the muscle (Grass SD9). Stimulation parameters followed those established previously for transilluminated, striated muscle preparations (34,36), and assessments of both mechanical and perfusion responses were determined immediately following cessation of the electrical stimulation. All procedures were performed under control conditions in LZR and OZR, and following treatment of the in situ cremaster muscle with Tempol (10 Ϫ3 M), SQ-29548 (10 Ϫ4 M), and/or phentolamine (10 Ϫ5 M) within the superfusate solution.…”
Section: Animalsmentioning
confidence: 99%
“…With continued hyperphagia, OZR become progressively insulin-resistant, dyslipidemic (hypercholesterolemia and severe hypertriglyceridemia) and moderately hypertensive (5, 18). As such, the OZR represents a complete model of the metabolic syndrome and, owing to the origin in a chronic excess caloric intake, an appropriate and relevant model for the human condition.Previous study from our laboratory and by others has demonstrated that multiple relevant pathways of both dilator and constrictor reactivity are altered in OZR with development of the metabolic syndrome, and this can contribute to an impaired ability to effectively match skeletal muscle perfusion with metabolic demand (10,11,34,35,36). Among these impacted pathways are those of endothelium-dependent origin, such as wall shear rate (3, 15), reduced PO 2 (16,17), and an array of pharmacological challenges, including acetylcholine (15) and arachidonic acid (17,(35)(36)(37).…”
mentioning
confidence: 97%
See 1 more Smart Citation